2019
DOI: 10.1093/fampra/cmz026
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported depression treatment and future treatment preferences: an observational study in general practice

Abstract: Background Depression is prevalent in general practice, but few studies have explored patient-reported depression care. Aim To investigate patient-reported treatment received for depression and future treatment preferences among adult patients visiting their GP, and to evaluate the associations with sex, age and educational level. Design and Setting A cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…A survey among patients in GP waiting rooms in Norway showed that lower educational level was associated with greater preference for medication. 35 The association between educational level and drug treatment found in our study among women only, may suggest that highly educated women are more skeptical to medication in general. This may apply particularly to younger women since older women in the study population were less educated.…”
Section: Comparison With Existing Literaturementioning
confidence: 54%
“…A survey among patients in GP waiting rooms in Norway showed that lower educational level was associated with greater preference for medication. 35 The association between educational level and drug treatment found in our study among women only, may suggest that highly educated women are more skeptical to medication in general. This may apply particularly to younger women since older women in the study population were less educated.…”
Section: Comparison With Existing Literaturementioning
confidence: 54%
“…A survey among patients in GP waiting rooms in Norway showed that lower educational level was associated with greater preference for medication. 34 The association between educational level and drug treatment found in the present Hansen AB et al BJGP Open 2021; DOI: 10.3399/BJGPO-2020-0122 study among women only, may suggest that highly educated women are more sceptical towards medication in general. This may apply particularly to younger women since older women in the study population were less educated.…”
Section: Comparison With Existing Literaturementioning
confidence: 65%
“… 54 , 55 Nonetheless, observational data of 28,498 patients referred for psychotherapy showed that patients with long-term somatic illnesses had similar outcomes compared to those without somatic comorbidity, excepted those with musculoskeletal condition, chronic obstructive pulmonary disease, and diabetes, considering that cases with somatic comorbidity needed more therapy sessions to achieve the same results. 56 , 57 …”
Section: Epidemiologymentioning
confidence: 99%